2019
DOI: 10.3389/fmicb.2019.02598
|View full text |Cite
|
Sign up to set email alerts
|

The E-Cadherin Cleavage Associated to Pathogenic Bacteria Infections Can Favor Bacterial Invasion and Transmigration, Dysregulation of the Immune Response and Cancer Induction in Humans

Abstract: Once bound to the epithelium, pathogenic bacteria have to cross epithelial barriers to invade their human host. In order to achieve this goal, they have to destroy the adherens junctions insured by cell adhesion molecules (CAM), such as E-cadherin (E-cad). The invasive bacteria use more or less sophisticated mechanisms aimed to deregulate CAM genes expression or to modulate the cell-surface expression of CAM proteins, which are otherwise rigorously regulated by a molecular crosstalk essential for homeostasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 228 publications
(243 reference statements)
2
54
0
3
Order By: Relevance
“…In a murine model, it was found that GVHD may be inhibited by preventing CD8 + CTL migration into the Peyer's patch either by disrupting the gene encoding the CCR5 chemokine receptor or by blocking the integrin α4β7-mucosal vascular addressin (MAdCAM-1) interaction into the gut Peyer's patches (Murai et al, 2003). Since mutants in the integrin α4β7 can also affect the integrin binding to E-cadherin (Higgins et al, 2000), it remains possible that such mutants might also affect the anti-bacterial CTL immune response through aberrant homing signals that involve E-cadherin, soluble E-cadherin, CD103, and KLRG1, as previously suggested (Devaux et al, 2019).…”
Section: Microbiota and The Innate Immunity: Relationship To Gvhdmentioning
confidence: 87%
See 3 more Smart Citations
“…In a murine model, it was found that GVHD may be inhibited by preventing CD8 + CTL migration into the Peyer's patch either by disrupting the gene encoding the CCR5 chemokine receptor or by blocking the integrin α4β7-mucosal vascular addressin (MAdCAM-1) interaction into the gut Peyer's patches (Murai et al, 2003). Since mutants in the integrin α4β7 can also affect the integrin binding to E-cadherin (Higgins et al, 2000), it remains possible that such mutants might also affect the anti-bacterial CTL immune response through aberrant homing signals that involve E-cadherin, soluble E-cadherin, CD103, and KLRG1, as previously suggested (Devaux et al, 2019).…”
Section: Microbiota and The Innate Immunity: Relationship To Gvhdmentioning
confidence: 87%
“…According to the UniProt database 1 , En. faecalis also encodes a predicted htrA protein serine protease, another candidate sheddase (Devaux et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several molecules produced by trophoblasts are candidate to affect differentiation of placental macrophages into MGCs. They include syncytins [ 46 , 47 ], E-cadherin and IL-4, a cytokine that mediates macrophage fusion in an E-cadherin-dependent manner [ 44 , 48 ]. The functions of placental MGCs are still obscure relying on indirect evidence.…”
Section: Placental Macrophages and Multinucleated Giant Cells: A Contmentioning
confidence: 99%